How customer and product orientations shape political brands. Issue 4 (18th July 2016) - Bigi, Alessandro; Treen, Emily; Bal, Anjali
Abstract : Purpose: A theory of consumer and product orientation is used in order to strategize about how politicians better position and present themselves to voters. It is evident that some politicians play an active role in shaping the beliefs and actions of their constituents while others are more influenced by voter sentiment. The effectiveness of the political strategy is highly influenced by the market realities of the voting body in question. Design/methodology/approach: A dichotomy is presented to shed light on how consumer and product orientation might influence the way in which politicians choose to address the public. Specifically, four modified strategic orientation archetypes are presented and analyzed with particular focus on political brands and strategy. Findings: Product and consumer orientations have been shown to also be applicable to the strategic positioning of political brands. While it can be argued that no strategy is superior over another, careful consideration of the political environment in question and subsequent execution of an appropriate stance can be used to better manage the relationship between the electorate and politicians. Research limitations/implications: This study provides academics in this area with a comprehensive examination of strategic orientation literature in political contexts, and lays out a strong groundwork for future studies. In this burgeoning area of research, there are several opportunities for marketing and political strategy academics to dive deeper into the intricacies that drive politicians to adopt specific strategic orientations, and how these strategies evolve over time and in differing political environments. Practical implications: This analysis suggests that there are opportunities for political strategists to explore the relationship between the identified strategic orientations and political brands, and for political marketing scholars to investigate the modes of focus presented. Originality/value: This analysis provides better understanding of how politicians can influence voters and voters can influence political brands, and how the strategic orientation archetypes can be used to influence decisions about political strategy.